Analisis Kebutuhan Awal Penuntun Praktikum Kimia Berbasis Green Chemistry untuk Mencapai Keamanan di Dalam Laboratorium - Yudha, Sandy; Nurfajriani, Nurfajriani (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
The 2013 Curriculum System requires students to play an active role in the learning process at school and study independently. So it is necessary to have learning media that can help students understand chemistry learning. Chemistry is a natural science that is both a product and a concept so that learning can be done through practicum activities. Practicum activities require a device as a guide in scientific work called a practical guidebook. This study uses a qualitative descriptive approach, which describes descriptively the results of the analysis carried out. The stages are as follows: the interview stage was conducted with Chemistry subject teachers to obtain data in the form of the use of practicum instructions that have been used so far and hopes for improvement. The second stage of the analysis was carried out using a questionnaire given to students to see how the practicum teaching and learning process was doing at school so far. This research involved students of class XI IPA Al-Azhar Private High School Medan. Based on the results of the research and discussion that have been described, it is concluded that the chemistry practicum guide that has been used so far at Madrasah Aliyah Al Washliyah Kedaisianam has not met the criteria. In the implementation of chemistry practicum students have not used a special practicum module, but only used the modules available in the package book